A participatory spatial risk assessment of green turtles (Chelonia mydas) with indigenous rangers in northern Australia - Natalie Robson; Alana Grech; Michele Thums; Joanna Day; Garnet Hooper; Carol Palmer; Sam Banks (Biodiversity and Conservation, 2026)
Coastal marine species and ecosystems face increasing pressure from anthropogenic threats. Green turtles ( Chelonia mydas ), listed as Vulnerable in Australia, are ecologically important and culturally significant for Indigenous Traditional Owners. This study co-developed a spatial risk assessment with eight Indigenous ranger groups to assess threats to green turtles in waters of Australia’s Northern Territory. Six anthropogenic hazards (comprising 11 threats) were mapped and combined with turtle occupancy, derived from the satellite tracks of 45 green turtles, to quantify threat exposure. Expert knowledge from Indigenous rangers on the impact and occurrence of 24 threats was combined to assess turtle vulnerability, generating a spatially explicit map of relative risk. Darwin Harbour had the highest concentration of overlapping threats, including artificial light, recreational vessels, oil infrastructure and shipping. Turtle vulnerability varied by region, reflecting local knowledge. Nest predation (West Arnhem, Tiwi Islands), sea-level rise, traditional hunting and industrial pollution had the highest threat scores. Foraging turtles were concentrated in eight areas, and Channel Island (Darwin Harbour) posed the highest relative risk for foraging turtles. Migration routes near Darwin Harbour and Bynoe Harbour were risk hotspots. Mixed-effects analyses showed that perceived vulnerability was structured primarily by threat type, with ranger experience contributing to variation in threat perceptions, highlighting the importance of retaining experienced Indigenous rangers for effective place-based conservation. Integrating Indigenous knowledge with spatial data, the study identifies high-risk areas for a culturally and ecologically important species and supports targeted management and sustained investment in Indigenous ranger programs amid increasing climate and industrial pressures.

Responses of small mammals to prescribed low-intensity fire: Genetic insights from a northern Australian fire experiment - Alexander R. Carey; Georgina Neave; Teigan Cremona; Hugh F. Davies; Brett P. Murphy; Geoffrey J. Cary; Tiwi Rangers; Toby Barton; Sam C. Banks (Biological Conservation, 2025)

Regional conservation genomics: insights and opportunities from northern Australia - Teigan Cremona; Brenton von Takach; Robyn Shaw; Alexander Carey; Bridget Campbell; Skye Cameron; Renee Catullo; Caroline Chong; Saul Cowen; Danielle Edwards; Emilie Ens; Tony Griffiths; et al. (Biodiversity and Conservation, 2025)
Biodiversity conservation in northern Australia is characterised by high endemism, data deficiency, and high Indigenous land tenure and population. The Northern Australia Conservation Genomics Forum brought together experts to explore current genetic research with particular emphasis on integration of genomics within conservation practices. We discuss the regional biodiversity of northern Australia, highlighting the unique biogeographic patterns, known and unknown species diversity, and ongoing threats such as habitat degradation, altered fire regimes, invasive species, and climate change. This article synthesises key themes from the forum, including the current application of genomics in conservation, gaps and areas of need and opportunity to advance species conservation in this sparsely populated, yet iconic region of Australia. We highlight the need to expand collaborative research partnerships across land tenures with Indigenous organisations, pastoralists, government and non-government organisations, which is crucial for the effective study and conservation of the region’s biodiversity. The paper identifies the challenges and opportunities in applying genomic data to conservation strategies and applied management, including species translocations and habitat management, while acknowledging the limitations and gaps in current research and collections. The insights from this forum emphasise the advantages in using genomics to inform conservation decisions, and the need for continued research and collaboration to protect northern Australia’s unique biodiversity.

Declines in greater bilby (Macrotis lagotis) geographic range and realised niche are best explained by the invasive red fox (Vulpes vulpes) - Hayley M. Geyle; Alys R. Young; Brett P. Murphy; Chris R. Dickman; Christine Schlesinger; Kelly M. Dixon; Harry Moore; Sarah Legge; Jennifer Silcock; Naomi Indigo; Martin Dziminski; Bruce Greatwich; et al. (Biological Conservation, 2025)

Genetic relatedness shapes social dynamics in a threatened finch: implications for population assessment - Mara F. Müller; Cameron J. Baker; Sam C. Banks; Mariana A. Campbell; Tara L. Crewe; Mirjam Kaestli; Sydney J. Collett; Ian J. Radford; Hamish A. Campbell (Animal Behaviour, 2025)

Building meaningful collaboration in conservation genetics and genomics - Robyn E. Shaw; Brittany Brockett; Jennifer C. Pierson; Stephen D. Sarre; Paula Doyle; Hannah B. Cliff; Mark D. B. Eldridge; Kimberly A. Miller; Kym Ottewell; Marissa L. Parrott; Maurizio Rossetto; Paul Sunnucks; et al. (Conservation Genetics, 2024)
Genetic diversity is the foundation of biodiversity, and preserving it is therefore fundamental to conservation practice. However, global conservation efforts face significant challenges integrating genetic and genomic approaches into applied management and policy. As collaborative partnerships are increasingly recognized as key components of successful conservation efforts, we explore their role and relevance in the Australian context, by engaging with key entities from across the conservation sector, including academia, botanic gardens, herbaria, seed banks, governmental/non-governmental organisations, private industry, museums, Traditional Owners, Indigenous rangers, and zoos and aquaria. By combining perspectives from these entities with comprehensive literature review, we identified five guiding principles for conservation genetic and genomic research and explored the different elements of, and approaches to, collaboration. Our reflections suggest that there is a substantial overlap in research interests across the Australian conservation sector, and our findings show that collaboration is increasing. We discuss approaches to building collaborative partnerships, the reciprocal benefits of collaborating, and some remaining challenges associated with data generation, data collection, and cross-cultural considerations. We emphasise the need for long-term national resourcing for sample and data storage and consistency in collecting, generating and reporting genetic data. While informed by the Australian experience, our goal is to support researchers and practitioners to foster meaningful collaborations that achieve measurable management outcomes in conservation genetics and genomics, both in Australia and globally.

Conservation prioritisation of genomic diversity to inform management of a declining mammal species - Brenton von Takach; Skye F. Cameron; Teigan Cremona; Mark D.B. Eldridge; Diana O. Fisher; Rosemary Hohnen; Chris J. Jolly; Ella Kelly; Ben L. Phillips; Ian J. Radford; Kate Rick; Peter B.S. Spencer; et al. (Biological Conservation, 2024)

The ethics of intervening in animal behaviour for conservation - Thom van Dooren; Catherine J. Price; Peter B. Banks; Oded Berger-Tal; Matthew Chrulew; Jane Johnson; Gabrielle Lajeunesse; Kate E. Lynch; Clare McArthur; Finn C.G. Parker; Myles Oakey; Benjamin J. Pitcher; et al. (Trends in Ecology & Evolution, 2023)

Pyrodiversity trade-offs: A simulation study of the effects of fire size and dispersal ability on native mammal populations in northern Australian savannas - Hugh F. Davies; Casey Visintin; Brett P. Murphy; Euan G. Ritchie; Sam C. Banks; Ian D. Davies; David M.J.S. Bowman (Biological Conservation, 2023)

Evidence of resident coastal population(s) of false killer whales (Pseudorca crassidens) in northern Australian waters - Carol Palmer; Karen K. Martien; Holly Raudino; Kelly M. Robertson; Alan Withers; Emma Withers; Robert Risk; Dylan Cooper; Ellen D’Cruz; Edmund Jungine; Daniel Barrow; Nick Cuff; et al. (Frontiers in Marine Science, 2023)
To help evaluate the distribution, residency, population size and structuring (and hence conservation status) of the poorly known false killer whale Pseudorca crassidens in northern Australian waters, we undertook studies of sightings, movement patterns based on satellite telemetry, and genetics. Sighting data indicates that false killer whales are regular, year-round inhabitants of coastal areas of northern Australia. Satellite-tagged animals spent extended periods of time in shallow coastal waters, with no tagged animals leaving the continental shelf. The lack of spatial overlap in the areas visited by individuals tagged in the Arafura/Timor Seas compared to those tagged in the Gulf of Carpentaria suggests that there may be more than one population in northern Australia coastal waters. All 14 genetic samples collected across 1600 km of coastline possessed the same newly identified mitochondrial control region haplotype, designated haplotype 45. Notably, haplotype 45 is distinct from all previously published false killer whale haplotypes globally and is most similar to the two haplotypes that typify the endangered main Hawaiian Islands insular false killer whale population. Based on these results and evidence from recent movement records of those tagged, false killer whales in northern Australia are apparently demographically independent from the offshore population(s). Further assessment of the population conservation status is now required.

Population genomics of a predatory mammal reveals patterns of decline and impacts of exposure to toxic toads - Brenton von Takach; Louis Ranjard; Christopher P. Burridge; Skye F. Cameron; Teigan Cremona; Mark D. B. Eldridge; Diana O. Fisher; Stephen Frankenberg; Brydie M. Hill; Rosemary Hohnen; Chris J. Jolly; Ella Kelly; et al. (Molecular Ecology, 2022)
Mammal declines across northern Australia are one of the major biodiversity loss events occurring globally. There has been no regional assessment of the implications of these species declines for genomic diversity. To address this, we conducted a species‐wide assessment of genomic diversity in the northern quoll ( Dasyurus hallucatus ), an Endangered marsupial carnivore. We used next generation sequencing methods to genotype 10,191 single nucleotide polymorphisms (SNPs) in 352 individuals from across a 3220‐km length of the continent, investigating patterns of population genomic structure and diversity, and identifying loci showing signals of putative selection. We found strong heterogeneity in the distribution of genomic diversity across the continent, characterized by (i) biogeographical barriers driving hierarchical population structure through long‐term isolation, and (ii) severe reductions in diversity resulting from population declines, exacerbated by the spread of introduced toxic cane toads ( Rhinella marina ). These results warn of a large ongoing loss of genomic diversity and associated adaptive capacity as mammals decline across northern Australia. Encouragingly, populations of the northern quoll established on toad‐free islands by translocations appear to have maintained most of the initial genomic diversity after 16 years. By mapping patterns of genomic diversity within and among populations, and investigating these patterns in the context of population declines, we can provide conservation managers with data critical to informed decision‐making. This includes the identification of populations that are candidates for genetic management, the importance of remnant island and insurance/translocated populations for the conservation of genetic diversity, and the characterization of putative evolutionarily significant units.

Sex and male breeding state predict intraspecific trait variation in mouth‐brooding fishes - Janine E. Abecia; Osmar J. Luiz; David A. Crook; Sam C. Banks; Dion Wedd; Alison J. King (Journal of Fish Biology, 2022)
Sex‐specific reproductive roles contribute to sexual dimorphic morphological trait variations. In uniparental mouth‐brooding fishes, the mouth performs a reproductive function in addition to its key roles in feeding and respiration, resulting in the potential for sex‐specific functional performance trade‐offs. Trait differences related to parental care may occur when the individual matures or be restricted to periods when the parent is mouth‐brooding. This study explored sexual dimorphism and morphological trait adaptations related to feeding, breeding, respiration and locomotion performance in two paternal mouth‐brooding freshwater fishes ( Glossamia aprion and Neoarius graeffei ). Eight morphological traits were evaluated for sexual dimorphism (non‐brooder males vs. females) and male breeding state differences (brooders vs. non‐brooders). Male breeding state was a significant predictor of trait variation in both species. Brooders differed in buccal volume and in several feeding and locomotory traits compared to non‐brooder males. Non‐brooder males had bigger buccal volumes and relative eye diameters ( G. aprion ) and larger relative gape sizes ( N. graeffei ) compared to females, a potential response to both mouth‐brooding and feeding requirements. Although there were clear trait differences between brooder and non‐brooder males, further research is required to confirm whether individuals return to their former morphology once mouth‐brooding has ceased or if trait differences are maintained post‐brooding. This study highlights the importance of considering the potential impacts of intraspecific trait variation on the performance of critical life functions, such as feeding, respiration and locomotion across the life history.

Non-invasive genetic sampling is one of our most powerful and ethical tools for threatened species population monitoring: a reply to Lavery et al. - Sam C. Banks; Maxine P. Piggott (Biodiversity and Conservation, 2022)
Noninvasive genetic sampling (genetic tagging) of individuals is one of the most powerful and ethical tools for threatened species population monitoring. A recent review of the threats to Australia’s rock-wallabies ( Petrogale spp.) and the methods for their monitoring stated that noninvasive genetic sampling (faecal DNA analysis) is not viable for estimating population size and trends for species in this genus. We feel that it is important to respond as such statements have the potential to stifle the development and application of an important tool for threatened species monitoring and lead to lost opportunities for collection of high-quality data to inform conservation of these species. We take the opportunity to describe the breadth of successful application of noninvasive genetic sampling for monitoring rock wallabies and other mammal taxa, the research and development requirements for successful implementation of noninvasive DNA-based population monitoring and thoughts on why this powerful approach has not been implemented to its full potential in many jurisdictions. We need to be careful not to dismiss one of the most powerful and ethical threatened species monitoring tools due to lack of familiarity with the requirements for its implementation.

Environmental resistance and habitat quality influence dispersal of the saltwater crocodile - Yusuke Fukuda; Craig Moritz; Namchul Jang; Grahame Webb; Hamish Campbell; Keith Christian; Garry Lindner; Sam Banks (Molecular Ecology, 2022)
Landscape genetics commonly focuses on the effects of environmental resistance on animal dispersal patterns, but there is an emerging focus on testing environmental effects on emigration and settlement choices. In this study, we used landscape genetics approaches to quantify dispersal patterns in the world's largest crocodilian, the saltwater crocodile ( Crocodylus porosus ), and demonstrated environmental influences on three processes that comprise dispersal: emigration, movement and settlement. We found that both environmental resistance and properties of the source and destination catchments (proportion of breeding habitat) were important factors influencing observed dispersal events. Our habitat quality variables related to hypotheses about resource competition and represented the ratio of breeding habitat (which limits carrying capacity), suggesting that competition for habitat influences emigration and settlement choices, together with the strong effect of environmental resistance to movement (where high‐quality habitat was associated with greatest environmental permeability). Approximately 42% of crocodiles were migrants from populations other than their sampling locations and some outstandingly productive populations had a much higher proportion of emigration rather than immigration. The distance most commonly travelled between source and destination was 150–200 km although a few travelled much longer distances, up to 600–700 km. Given the extensive dispersal range, individual catchments or hydrographic regions that combine two or three adjacent catchments are an appropriate scale for population management.

Disturbance alters the forest soil microbiome - Elle J. Bowd; Sam C. Banks; Andrew Bissett; Tom W. May; David B. Lindenmayer (Molecular Ecology, 2022)
Billions of microorganisms perform critical below‐ground functions in all terrestrial ecosystems. While largely invisible to the naked eye, they support all higher lifeforms, form symbiotic relationships with ~90% of terrestrial plant species, stabilize soils, and facilitate biogeochemical cycles. Global increases in the frequency of disturbances are driving major changes in the structure and function of forests. However, despite their functional significance, the disturbance responses of forest microbial communities are poorly understood. Here, we explore the influence of disturbance on the soil microbiome (archaea, fungi and bacteria) of some of the world's tallest and most carbon‐dense forests, the Mountain Ash forests of south‐eastern Australia. From 80 sites, we identified 23,277 and 19,056 microbial operational taxonomic units from the 0–10 cm and 20–30 cm depths of soil respectively. From this extensive data set, we found the diversity and composition of these often cryptic communities has been altered by human and natural disturbance events. For instance, the diversity of ectomycorrhizal fungi declined with clearcut logging, the diversity of archaea declined with salvage logging, and bacterial diversity and overall microbial diversity declined with the number of fires. Moreover, we identified key associations between edaphic (soil properties), environmental (slope, elevation) and spatial variables and the composition of all microbial communities. Specifically, we found that soil pH, manganese, magnesium, phosphorus, iron and nitrate were associated with the composition of all microbial communities. In a period of widespread degradation of global forest ecosystems, our findings provide an important and timely insight into the disturbance responses of soil microbial communities, which may influence key ecological functions.

The origin and composition of carbonatite-derived carbonate-bearing fluorapatite deposits - Sam Broom-Fendley; Pete R. Siegfried; Frances Wall; Mary O’Neill; Richard A. Brooker; Emily K. Fallon; Jonathan R. Pickles; David A. Banks (Mineralium Deposita, 2021)
Carbonate-bearing fluorapatite rocks occur at over 30 globally distributed carbonatite complexes and represent a substantial potential supply of phosphorus for the fertiliser industry. However, the process(es) involved in forming carbonate-bearing fluorapatite at some carbonatites remain equivocal, with both hydrothermal and weathering mechanisms inferred. In this contribution, we compare the paragenesis and trace element contents of carbonate-bearing fluorapatite rocks from the Kovdor, Sokli, Bukusu, Catalão I and Glenover carbonatites in order to further understand their origin, as well as to comment upon the concentration of elements that may be deleterious to fertiliser production. The paragenesis of apatite from each deposit is broadly equivalent, comprising residual magmatic grains overgrown by several different stages of carbonate-bearing fluorapatite. The first forms epitactic overgrowths on residual magmatic grains, followed by the formation of massive apatite which, in turn, is cross-cut by late euhedral and colloform apatite generations. Compositionally, the paragenetic sequence corresponds to a substantial decrease in the concentration of rare earth elements (REE), Sr, Na and Th, with an increase in U and Cd. The carbonate-bearing fluorapatite exhibits a negative Ce anomaly, attributed to oxic conditions in a surficial environment and, in combination with the textural and compositional commonality, supports a weathering origin for these rocks. Carbonate-bearing fluorapatite has Th contents which are several orders of magnitude lower than magmatic apatite grains, potentially making such apatite a more environmentally attractive feedstock for the fertiliser industry. Uranium and cadmium contents are higher in carbonate-bearing fluorapatite than magmatic carbonatite apatite, but are much lower than most marine phosphorites.

Prioritising source populations for supplementing genetic diversity of reintroduced southern brown bandicoots Isoodon obesulus obesulus - Natasha M. Robinson; Chloe Rhoades; Jennifer Pierson; David B. Lindenmayer; Sam C. Banks (Conservation Genetics, 2021)

Direct and indirect disturbance impacts in forests - Elle J. Bowd; Sam C. Banks; Andrew Bissett; Tom W. May; David B. Lindenmayer (Ecology Letters, 2021)
Human and natural disturbances are key drivers of change in forest ecosystems. Yet, the direct and indirect mechanisms which underpin these changes remain poorly understood at the ecosystem level. Here, using structural equation modelling across a 150+ year chronosequence, we disentangle the direct and indirect effects of major disturbances in a temperate forest ecosystem. We show that wildfires, logging and post‐fire (salvage) logging can affect plant and microbial communities and abiotic soil properties both directly and indirectly through plant–soil–microbial interactions. We quantified 68 direct and indirect disturbance effects across these components, with the majority resulting in ecosystem‐wide adverse effects. Indirect disturbance effects accounted for 43% of total disturbance effects, with some amplifying or partially mitigating direct disturbance effects. Overall, human disturbances were associated with more negative effects than natural disturbances. Our analyses provide novel insights into the multifaceted dynamics of forest disturbances and the mechanisms which underpin their relative impacts.

Scale‐dependent signatures of local adaptation in a foundation tree species - Brenton von Takach; Collin W. Ahrens; David B. Lindenmayer; Sam C. Banks (Molecular Ecology, 2021)
Understanding local adaptation is critical for conservation management under rapidly changing environmental conditions. Local adaptation inferred from genotype‐environment associations may show different genomic patterns depending on the spatial scale of sampling, due to differences in the slope of environmental gradients and the level of gene flow. We compared signatures of local adaptation across the genome of mountain ash ( Eucalyptus regnans ) at two spatial scales: A species‐wide data set and a topographically‐complex subregional data set. We genotyped 367 individual trees at over 3700 single‐nucleotide polymorphisms (SNPs), quantified patterns of spatial genetic structure among populations, and used two analytical methods to identify loci associated with at least one of three environmental variables at each spatial scale. Together, the analyses identified 549 potentially adaptive SNPs at the subregion scale, and 435 SNPs at the range‐wide scale. A total of 39 genic or near‐genic SNPs, associated with 28 genes, were identified at both spatial scales, although no SNP was identified by both methods at both scales. We observed that nongenic regions had significantly higher homozygote excess than genic regions, possibly due to selective elimination of inbred genotypes during stand development. Our results suggest that strong environmental selection occurs in mountain ash, and that the identification of putatively adaptive loci can differ substantially depending on the spatial scale of analyses. We also highlight the importance of multiple adaptive genetic architectures for understanding patterns of local adaptation across large heterogenous landscapes, with comparison of putatively adaptive loci among spatial scales providing crucial insights into the process of adaptation.

The influence of fire and silvicultural practices on the landscape-scale genetic structure of an Australian foundation tree species - Brenton von Takach Dukai; Rod Peakall; David B. Lindenmayer; Sam C. Banks (Conservation Genetics, 2020)

Transition to density dependence in a reintroduced ecosystem engineer - Adrian D. Manning; Maldwyn J. Evans; Sam C. Banks; William G. Batson; Emily Belton; Helen A. Crisp; Donald B. Fletcher; Iain J. Gordon; Kate Grarock; Nicki Munro; Jenny Newport; Jennifer Pierson; et al. (Biodiversity and Conservation, 2019)

The impact of mating systems and dispersal on fine‐scale genetic structure at maternally, paternally and biparentally inherited markers - Robyn E. Shaw; Sam C. Banks; Rod Peakall (Molecular Ecology, 2018)
For decades, studies have focused on how dispersal and mating systems influence genetic structure across populations or social groups. However, we still lack a thorough understanding of how these processes and their interaction shape spatial genetic patterns over a finer scale (tens—hundreds of metres). Using uniparentally inherited markers may help answer these questions, yet their potential has not been fully explored. Here, we use individual‐level simulations to investigate the effects of dispersal and mating system on fine‐scale genetic structure at autosomal, mitochondrial and Y chromosome markers. Using genetic spatial autocorrelation analysis, we found that dispersal was the major driver of fine‐scale genetic structure across maternally, paternally and biparentally inherited markers. However, when dispersal was restricted (mean distance = 100 m), variation in mating behaviour created strong differences in the comparative level of structure detected at maternally and paternally inherited markers. Promiscuity reduced spatial genetic structure at Y chromosome loci (relative to monogamy), whereas structure increased under polygyny. In contrast, mitochondrial and autosomal markers were robust to differences in the specific mating system, although genetic structure increased across all markers when reproductive success was skewed towards fewer individuals. Comparing males and females at Y chromosome vs. mitochondrial markers, respectively, revealed that some mating systems can generate similar patterns to those expected under sex‐biased dispersal. This demonstrates the need for caution when inferring ecological and behavioural processes from genetic results. Comparing patterns between the sexes, across a range of marker types, may help us tease apart the processes shaping fine‐scale genetic structure.

When can refuges mediate the genetic effects of fire regimes? A simulation study of the effects of topography and weather on neutral and adaptive genetic diversity in fire‐prone landscapes - Sam C. Banks; Ian D. Davies; Geoffrey J. Cary (Molecular Ecology, 2017)
Understanding how landscape heterogeneity mediates the effects of fire on biodiversity is increasingly important under global changes in fire regimes. We used a simulation experiment to investigate how fire regimes interact with topography and weather to shape neutral and selection‐driven genetic diversity under alternative dispersal scenarios, and to explore the conditions under which microrefuges can maintain genetic diversity of populations exposed to recurrent fire. Spatial heterogeneity in simulated fire frequency occurred in topographically complex landscapes, with fire refuges and fire‐prone “hotspots” apparent. Interannual weather variability reduced the effect of topography on fire patterns, with refuges less apparent under high weather variability. Neutral genetic diversity was correlated with long‐term fire frequency under spatially heterogeneous fire regimes, being higher in fire refuges than fire‐prone areas, except under high dispersal or low fire severity (low mortality). This generated different spatial genetic structures in fire‐prone and fire‐refuge components of the landscape, despite similar dispersal. In contrast, genetic diversity was only associated with time since the most recent fire in flat landscapes without predictable refuges and hotspots. Genetic effects of selection driven by fire‐related conditions depended on selection pressure, migration distance and spatial heterogeneity in fire regimes. Allele frequencies at a locus conferring higher fitness under successional environmental conditions followed a pattern of “temporal adaptation” to contemporary conditions under strong selection pressure and high migration. However, selected allele frequencies were correlated with spatial variation in long‐term mean fire frequency (relating to environmental predictability) under weak dispersal, low selection pressure and strong spatial heterogeneity in fire regimes.

Disease-associated change in an amphibian life-history trait - Benjamin C. Scheele; Lee F. Skerratt; David A. Hunter; Sam C. Banks; Jennifer C. Pierson; Don A. Driscoll; Philip G. Byrne; Lee Berger (Oecologia, 2017)

Short‐ and long‐term effects of habitat fragmentation differ but are predicted by response to the matrix - Maldwyn J. Evans; Sam C. Banks; Don A. Driscoll; Andrew J. Hicks; Brett A. Melbourne; Kendi F. Davies (Ecology, 2017)
Habitat loss and fragmentation are major threats to biodiversity and ecosystem processes. Our current understanding of the impacts of habitat loss and fragmentation is based largely on studies that focus on either short‐term or long‐term responses. Short‐term responses are often used to predict long‐term responses and make management decisions. The lack of studies comparing short‐ and long‐term responses to fragmentation means we do not adequately understand when and how well short‐term responses can be extrapolated to predict long‐term responses, and when or why they cannot. To address this gap, we used data from one of the world's longest‐running fragmentation experiments, The Wog Wog Habitat Fragmentation Experiment. Using data for carabid beetles, we found that responses in the long term (more than 22 yr post‐fragmentation ≈22 generations) often contrasted markedly with those in the short term (5 yr post‐fragmentation). The total abundance of all carabids, species richness and the occurrence of six species declined in the short term in the fragments but increased over the long term. The occurrence of three species declined initially and continued to decline, whilst another species was positively affected initially but decreased in the long term. Species’ responses to the matrix that surrounds the fragments strongly predicted both the direction (increase/decline in occurrence) and magnitude of their responses to fragmentation. Additionally, species’ responses to the matrix were somewhat predicted by their preferences for different types of native habitat (open vs. shaded). Our study highlights the degree of the matrix's influence in fragmented landscapes, and how this influence can change over time. We urge caution in using short‐term responses to forecast long‐term responses in cases where the matrix (1) impacts species’ responses to fragmentation (by isolating them, creating new habitat or altering fragment habitat) and (2) is likely to change through time.

The role of relatedness in mate choice by an arboreal marsupial in the presence of fine-scale genetic structure - Michaela D. J. Blyton; Robyn E. Shaw; Rod Peakall; David B. Lindenmayer; Sam C. Banks (Behavioral Ecology and Sociobiology, 2016)

Fine‐scale refuges can buffer demographic and genetic processes against short‐term climatic variation and disturbance: a 22‐year case study of an arboreal marsupial - Sam C. Banks; Thibault Lorin; Robyn E. Shaw; Lachlan McBurney; David Blair; Michaela D.J. Blyton; Annabel L. Smith; Jennifer C. Pierson; David B. Lindenmayer (Molecular Ecology, 2015)
Ecological disturbance and climate are key drivers of temporal dynamics in the demography and genetic diversity of natural populations. Microscale refuges are known to buffer species’ persistence against environmental change, but the effects of such refuges on demographic and genetic patterns in response to short‐term environmental variation are poorly understood. We quantified demographic and genetic responses of mountain brushtail possums ( Trichosurus cunninghami ) to rainfall variability (1992–2013) and to a major wildfire. We hypothesized that there would be underlying differences in demographic and genetic processes between an unburnt mesic refuge and a topographically exposed zone that was burnt in 2009. Fire caused a 2‐year decrease in survival in the burnt zone, but the population grew after the fire due to immigration, leading to increased expected heterozygosity. We documented a fire‐related behavioural shift, where the rate of movement by individuals in the unburnt refuge to the burnt zone decreased after fire. Irrespective of the fire, there were long‐term differences in demographic and genetic parameters between the mesic/unburnt refuge and the nonmesic/burnt zone. Survival was high and unaffected by rainfall in the refuge, but lower and rainfall‐dependent in the nonmesic zone. Net movement of individuals was directional, from the mesic refuge to the nonmesic zone, suggesting fine‐scale source–sink dynamics. There were higher expected heterozygosity ( H E ) and temporal genetic stability in the refuge, but lower H E and marked temporal genetic structure in the exposed habitat, consistent with reduced generational overlap caused by elevated mortality and immigration. Thus, fine‐scale refuges can mediate the short‐term demographic and genetic effects of climate and ecological disturbance.

The effect of sex‐biased dispersal on opposite‐sexed spatial genetic structure and inbreeding risk - Michaela D. J. Blyton; Sam C. Banks; Rod Peakall (Molecular Ecology, 2015)
Natal sex‐biased dispersal has long been thought to reduce the risk of inbreeding by spatially separating opposite‐sexed kin. Yet, comprehensive and quantitative evaluations of this hypothesis are lacking. In this study, we quantified the effectiveness of sex‐biased dispersal as an inbreeding avoidance strategy by combining spatially explicit simulations and empirical data. We quantified the extent of kin clustering by measuring the degree of spatial autocorrelation among opposite‐sexed individuals ( FM structure). This allowed us to systematically explore how the extent of sex‐biased dispersal, generational overlap, and mate searching distance, influenced both kin clustering, and the resulting inbreeding in the absence of complementary inbreeding avoidance strategies. Simulations revealed that when sex‐biased dispersal was limited, positive FM genetic structure developed quickly and increased as the mate searching distance decreased or as generational overlap increased. Interestingly, complete long‐range sex‐biased dispersal did not prevent the development of FM genetic structure when generations overlapped. We found a very strong correlation between FM genetic structure and both F IS under random mating, and pedigree‐based measures of inbreeding. Thus, we show that the detection of FM genetic structure can be a strong indicator of inbreeding risk. Empirical data for two species with different life history strategies yielded patterns congruent with our simulations. Our study illustrates a new application of spatial genetic autocorrelation analysis that offers a framework for quantifying the risk of inbreeding that is easily extendable to other species. Furthermore, our findings provide other researchers with a context for interpreting observed patterns of opposite‐sexed spatial genetic structure.

Priority effects can lead to underestimation of dispersal and invasion potential - Ceridwen I. Fraser; Sam C. Banks; Jonathan M. Waters (Biological Invasions, 2015)

Not all types of host contacts are equal when it comes to E. coli transmission - Michaela D.J. Blyton; Sam C. Banks; Rod Peakall; David B. Lindenmayer; David M. Gordon (Ecology Letters, 2014)
The specific processes that facilitate pathogen transmission are poorly understood, particularly for wild animal populations. A major impediment for investigating transmission pathways is the need for simultaneous information on host contacts and pathogen transfer. In this study, we used commensal Escherichia coli strains as a model system for gastrointestinal pathogens. We combined strain‐sharing information with detailed host contact data to investigate transmission routes in mountain brushtail possums. Despite E. coli being transmitted via the faecal‐oral route, we revealed that, strain‐sharing among possums was better explained by host contacts than spatial proximity. Furthermore, and unexpectedly, strain‐sharing was more strongly associated with the duration of brief nocturnal associations than day‐long den‐sharing. Thus, the most cryptic and difficult associations to measure were the most relevant connections for the transmission of this symbiont. We predict that future studies that employ similar approaches will reveal the importance of previously overlooked associations as key transmission pathways.

Dominant Drivers of Seedling Establishment in a Fire-Dependent Obligate Seeder: Climate or Fire Regimes? - Annabel L. Smith; David Blair; Lachlan McBurney; Sam C. Banks; Philip S. Barton; Wade Blanchard; Don A. Driscoll; A. Malcolm Gill; David B. Lindenmayer (Ecosystems, 2014)

Development of a powerful microsatellite marker panel for Trichosurus cunninghami - Michaela D. J. Blyton; Robyn Shaw; Sam C. Banks (Conservation Genetics Resources, 2014)

Functional genotypes are associated with commensal Escherichia coli strain abundance within host individuals and populations - Michaela D. J. Blyton; Sam C. Banks; Rod Peakall; David M. Gordon (Molecular Ecology, 2013)

Functional genotypes are associated with commensal Escherichia coli strain abundance within‐host individuals and populations - Michaela D. J. Blyton; Sam C. Banks; Rod Peakall; David M. Gordon (Molecular Ecology, 2013)
The selective pressures that determine genotype abundance and distribution frequently vary between ecological levels. Thus, it is often unclear whether the same functional genotypes will become abundant at different levels and how selection acting at these different scales is linked. In this study, we examined whether particular functional genotypes, defined by the presence or absence of 34 genes, of commensal E scherichia coli strains were associated with within‐host abundance and/or host population abundance in a wild population of 54 adult mountain brushtail possums ( T richosurus cunninghami) . Our results revealed that there was a positive correlation between a strain's relative abundance within individuals and the strain's abundance in the host population. We also found that strain abundance at both ecological levels was predicted by the same group of functional genes ( agn43 , focH , micH47, iroN , ygiL , ompT , kspmT2 and K1) that had associated patterns of occurrence. We propose that direct selection on the same functional genes at both levels may in part be responsible for the observed correlation between the ecological levels. However, a potential link between abundance within the host and excretion rate may also contribute.

High temporal variability in commensal E scherichia coli strain communities of a herbivorous marsupial - Michaela D. J. Blyton; Sam C. Banks; Rod Peakall; David M. Gordon (Environmental Microbiology, 2013)
Summary Although E scherichia coli is an important model organism for bacterial research, few studies have explored the nature of temporal variation in E . coli strains within the intestinal tracts of host individuals. In this study the E . coli strains of 54 mountain brushtail possums were sampled on four occasions during a year. This allowed temporal changes to be quantified both at the host population level and within individuals. E scherichia coli strains were identified using a combination of rep‐ PCR profiles from two primers ( CGG and ERIC ) and phylogenetic group assigned by quadruplex PCR . The study revealed considerable changes in community structure within individuals among all time periods. In fact, temporal variation within individuals accounted for more of the variation in E . coli community structure than differences between animals. In contrast to the within‐host dynamics, there were no significant differences among the time periods at the host population level. It was also found that there was no effect of host age or sex on strain community structure within host individuals. These findings highlight the importance of temporal variation in the ecology of E . coli , while the methods applied in this study may serve as a foundation for further work in this area.

Genetic spatial autocorrelation can readily detect sex‐biased dispersal - SAM C. BANKS; ROD PEAKALL (Molecular Ecology, 2012)
Sex‐biased dispersal is expected to generate differences in the fine‐scale genetic structure of males and females. Therefore, spatial analyses of multilocus genotypes may offer a powerful approach for detecting sex‐biased dispersal in natural populations. However, the effects of sex‐biased dispersal on fine‐scale genetic structure have not been explored. We used simulations and multilocus spatial autocorrelation analysis to investigate how sex‐biased dispersal influences fine‐scale genetic structure. We evaluated three statistical tests for detecting sex‐biased dispersal: bootstrap confidence intervals about autocorrelation r values and recently developed heterogeneity tests at the distance class and whole correlogram levels. Even modest sex bias in dispersal resulted in significantly different fine‐scale spatial autocorrelation patterns between the sexes. This was particularly evident when dispersal was strongly restricted in the less‐dispersing sex (mean distance n ≥ 250). However, there was variation in type I error rates among the tests, for which we offer specific recommendations. We found congruence between simulation predictions and empirical data from the agile antechinus, a species that exhibits male‐biased dispersal, confirming the power of individual‐based genetic analysis to provide insights into asymmetries in male and female dispersal. Our key recommendations for using multilocus spatial autocorrelation analyses to test for sex‐biased dispersal are: (i) maximize sample size, not locus number; (ii) concentrate sampling within the scale of positive structure; (iii) evaluate several distance class sizes; (iv) use appropriate methods when combining data from multiple populations; (v) compare the appropriate groups of individuals.

Adaptive responses and disruptive effects: how major wildfire influences kinship‐based social interactions in a forest marsupial - SAM C. BANKS; MICHAELA D. J. BLYTON; DAVID BLAIR; LACHLAN McBURNEY; DAVID B. LINDENMAYER (Molecular Ecology, 2012)
Environmental disturbance is predicted to play a key role in the evolution of animal social behaviour. This is because disturbance affects key factors underlying social systems, such as demography, resource availability and genetic structure. However, because natural disturbances are unpredictable there is little information on their effects on social behaviour in wild populations. Here, we investigated how a major wildfire affected cooperation (sharing of hollow trees) by a hollow‐dependent marsupial. We based two alternative social predictions on the impacts of fire on population density, genetic structure and resources. We predicted an adaptive social response from previous work showing that kin selection in den‐sharing develops as competition for den resources increases. Thus, kin selection should occur in burnt areas because the fire caused loss of the majority of hollow‐bearing trees, but no detectable mortality. Alternatively, fire may have a disruptive social effect , whereby postfire home range‐shifts ‘neutralize’ fine‐scale genetic structure, thereby removing opportunities for kin selection between neighbours. Both predictions occurred: the disruptive social effect in burnt habitat and the adaptive social response in adjacent unburnt habitat. The latter followed a massive demographic influx to unburnt ‘refuge’ habitat that increased competition for dens, leading to a density‐related kin selection response. Our results show remarkable short‐term plasticity of animal social behaviour and demonstrate how the social effects of disturbance extend into undisturbed habitat owing to landscape‐scale demographic shifts. We predicted long‐term changes in kinship‐based cooperative behaviour resulting from the genetic and resource impacts of forecast changes to fire regimes in these forests.

Using probability modelling and genetic parentage assignment to test the role of local mate availability in mating system variation - MICHAELA D. J. BLYTON; SAM C. BANKS; ROD PEAKALL; DAVID B. LINDENMAYER (Molecular Ecology, 2012)
The formal testing of mating system theories with empirical data is important for evaluating the relative importance of different processes in shaping mating systems in wild populations. Here, we present a generally applicable probability modelling framework to test the role of local mate availability in determining a population’s level of genetic monogamy. We provide a significance test for detecting departures in observed mating patterns from model expectations based on mate availability alone, allowing the presence and direction of behavioural effects to be inferred. The assessment of mate availability can be flexible and in this study it was based on population density, sex ratio and spatial arrangement. This approach provides a useful tool for (1) isolating the effect of mate availability in variable mating systems and (2) in combination with genetic parentage analyses, gaining insights into the nature of mating behaviours in elusive species. To illustrate this modelling approach, we have applied it to investigate the variable mating system of the mountain brushtail possum ( Trichosurus cunninghami ) and compared the model expectations with the outcomes of genetic parentage analysis over an 18‐year study. The observed level of monogamy was higher than predicted under the model. Thus, behavioural traits, such as mate guarding or selective mate choice, may increase the population level of monogamy. We show that combining genetic parentage data with probability modelling can facilitate an improved understanding of the complex interactions between behavioural adaptations and demographic dynamics in driving mating system variation.

Genetic structure of a recent climate change-driven range extension - SAM C. BANKS; SCOTT D. LING; CRAIG R. JOHNSON; MAXINE P. PIGGOTT; JANE E. WILLIAMSON; LUCIANO B. BEHEREGARAY (Molecular Ecology, 2010)

Adult survival and microsatellite diversity in possums: effects of major histocompatibility complex-linked microsatellite diversity but not multilocus inbreeding estimators - Sam C. Banks; Jean Dubach; Karen L. Viggers; David B. Lindenmayer (Oecologia, 2010)

Genetic marker investigation of the source and impact of predation on a highly endangered species - Sam C. Banks; Alan Horsup; Alan N. Wilton; Andrea C. Taylor (Molecular Ecology, 2003)
In September and October 2000, the remains of a number of apparently predated northern hairy‐nosed wombats ( Lasiorhinus krefftii ) were discovered in Epping Forest National Park, the site of the only known population of this highly endangered species. Analysis of DNA recovered from six carcasses and a section of intestine found nearby was carried out using microsatellite and Y‐specific primers. This identified seven individual wombats, the identity of three of which was inferred from a genotype database prepared from animals sampled during trapping programmes. Six victims were male and one female, suggesting that female‐biased predation rates are unlikely to be the cause of the current male‐biased population sex ratio. DNA isolated from four canid faeces found in the vicinity revealed three distinct canid microsatellite genotypes with very high probabilities of belonging to dingoes ( Canis familiaris dingo ). A wombat genotype matching that of one of the dead individuals was identified from scats of two of the dingoes. In addition, two macropod microsatellites were amplified from two dingo scats. These observations provided vital information regarding predation on northern hairy‐nosed wombats, and prompted the permanent exclusion of dingoes from the park by the erection of a dingo‐proof fence.

A set of microsatellite loci for the hairy-nosed wombats (Lasiorhinus krefftii and L. latifrons) - Luciano B. Beheregaray; Paul Sunnucks; Deryn L. Alpers; Sam C. Banks; Andrea C. Taylor (Conservation Genetics, 2000)